Rapid Assessment of Diverse Trichodermal Isolates of Indonesian Origin for Cellulase Production - Fahrurrozi Fahrurrozi; Shanti Ratnakomala; Trisanti Anindyawati; Puspita Lisdayanti; Endang Sukara (ANNALES BOGORIENSES, 2010)
Trichoderma is a well -known candidate to be promoted as cellulase producer  for the hidrolysis of lignocelluloses that contain  in  woody  biomass. The  number of trichodermal  isolates  in our  laboratory collected  from diverse ecosystem types in Indonesia increases significantly during the last 5 years. It is our aim to assess the cultures for its ability in producing cellulase. Sixty-six trichodermal isolates used in this experiment are obtained from Biotechnology Culture Collection (BTCC), Research Center for Biotechnology, Indonesian Institute of Sciences(LIPI)  The 31 isolates were isolated from District of Liwa (South Sumatra, Indonesia) and the 35 isolates from District of Maros (South Sulawesi, Indonesia). The  isolates were screened qualitatively,  7  isolates  from  Liwa and 12  isolates from Maros showed cellulolytic activity. From the results of quantitative test, two strains  (ID08-T004 and ID08-T63) showed the higher cellulolytic activity among the selected strains, 133.5 and 133.5 U/ml, respectively.  These  extracellular  enzymes  were  characterized  their  temperature  and  pH  optimum.  The temperature  optimum  for  both  enzymes  was  the  same,  50C,  with  activity  213.6  U/ml  for  enzyme  extracted from ID08-T004 and 197.3 U/ml for enzyme from ID08-T0063. The pH optimum was pH 5 of ID08-T004 with activity137.7 U/ml and pH 6 for ID08-T063 with activity 75.0 U/ml. The enzymes from ID08-T004 and ID08-T063 were stable in their temperature and pH optimal condition even after 90 minutes incubation with activity 179.0 U/ml and 86.7 U/ml, respectively. The enzyme stability was approximately 150 minutes for both enzymes in the temperature and pH optimum.   Key Words: Trichoderma, cellulase, Culture Collection